2019
DOI: 10.1101/642785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A 3500-year-old leaf from a Pharaonic tomb reveals that New Kingdom Egyptians were cultivating domesticated watermelon

Abstract: 19 Domestication of the watermelon (Citrullus lanatus) has alternatively been placed in South 20 Africa, the Nile valley, or more recently West Africa, with the oldest archeological evidence 21 coming from Libya and Egypt. The geographic origin and domestication of watermelons has 22 therefore remained unclear. Using extensive nuclear and plastid genomic data from a 3,560-23 year-old Citrullus leaf from a mummy's sarcophagus and skimmed genomes for 24 representatives of the seven extant species of Citrullus, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…A phylogenetic analysis of Citrullus (Chomicki & Renner, ), together with genetic, archaeological and historical data (reviewed by Paris, ) rejects the first two hypotheses, leaving West Africa and Northeast Africa. Phylogenomic analyses of nuclear gene sequences suggested that the white‐fleshed Sudanese Kordophan melon is the closest relative of the domesticated watermelon (Renner et al ., ; Fig. ).…”
Section: Time and Place Of Domesticationmentioning
confidence: 93%
See 1 more Smart Citation
“…A phylogenetic analysis of Citrullus (Chomicki & Renner, ), together with genetic, archaeological and historical data (reviewed by Paris, ) rejects the first two hypotheses, leaving West Africa and Northeast Africa. Phylogenomic analyses of nuclear gene sequences suggested that the white‐fleshed Sudanese Kordophan melon is the closest relative of the domesticated watermelon (Renner et al ., ; Fig. ).…”
Section: Time and Place Of Domesticationmentioning
confidence: 93%
“…The phylogeny results from a maximum likelihood (ML) analysis of 143 nuclear loci from Renner et al . () with ML bootstrap values shown at branches. ML analysis of a matrix with 100 plastid loci yielded the same topology, with high bootstrap support at all nodes.…”
Section: Time and Place Of Domesticationmentioning
confidence: 99%
“…The lack of haplotype divergence within C. lanatus and C. mucosospermus is likely the result of selection or other bottlenecks in the domestication histories of watermelon and egusi melon. Certainly, selection for sweet red-fleshed cultivars with high lycopene content or selection of seed type as source of protein/oil for consumption might contribute to current genetic structure in those cultivated species (Achigan-Dako et al, 2015;Renner et al, 2019).…”
Section: Genetic Diversity and Sequence Variationmentioning
confidence: 99%
“…Over the last two decades, questions regarding the origin and taxonomy ofCitrullus spp. have fuelled numerous studies to clarify phylogenetic relationships and nomenclature, identify wild relatives, and determine both centers of origin and divergence times (Jarret et al, 1997;Jarret & Newman, 2000;Levi et al, 2001;Levi et al, 2004;Levi & Thomas, 2005;Solmaz & Sari, 2009;Dje et al, 2010;Solmaz et al, 2010;Nesom, 2011;Levi et al, 2013;Mujaju et al, 2013;Hammer & Gladis, 2014;Chomicki & Renner, 2015;Renner et al, 2019;Chomicki et al, 2020). Despite these efforts, uncertainty vis-à-vis these questions remains as no wild relatives were found neither in west nor in northern east Africa; and comparatively few studies have focused on the distribution of the genetic variation within Citrullus or the likely colonization routes of various species within the genus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation